Asuhan Kebidanan Pada Ibu Hamil Trimester I Di PMB Nurwati Wilayah Kerja Puskesmas Air Tiris Tahun 2022 - Rahmanisa, Yosi; Erlinawati, Erlinawati (Evidence Midwifery Journal, 2023)
Midwifery care in pregnancy is an important factor that can affect the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). The pregnant woman Mrs. N experienced nausea, vomiting and low back pain during pregnancy. The purpose of this case is to study and provide midwifery care to pregnant women in the first trimester using the SOAP approach. This case study uses a descriptive observational design, data collection techniques were collected through interviews, physical examination and observation. The results of care for Mrs. N which was carried out on 02 August - 23 August 2022, namely pregnant women with nausea, vomiting and low back pain, the results of the mother's examination were within normal limits, BP: 110/80, N: 86x/minute, R: 20x/ minutes, S : 36.4 ? C, BW : 44 Kg, mother's conjunctiva pink, G1P0A0 11 weeks gestation, live fetus, single, intra-uterine, mother and fetus are in good condition, no signs of danger were found. The results of this case study are expected to add references that can be used for further research